KNOWLEDGE, ATTITUDE AND PRACTICE OF EMERGENCY CONTRACEPTION AMONGST HEALTHCARE WORKERS IN IDP CAMPS AND HOST COMMUNITY CLINICS IN JERE AND MAIDUGURI METROPOLITAN LOCAL GOVERNMENT AREAS, BORNO STATE, NIGERIA - Babagana Bako; Bala Mohammed Audu; Mohammed Bello Kawuwa; Asta Mana; Anna Peter (Ntec Specialist, 2021)
Background: Emergency contraception (EC) offers women a second chance to avoid unintended pregnancy after unprotected sexual intercourse. Besides its availability, requisite knowledge and positive attitude of the healthcare works will encourage its utilization by the Internally Displaced Persons (IDP) and host community. Objectives: To determine the knowledge, attitude and practice of EC by healthcare workers (HCWs) in IDP camps and host community clinics in Jere and Maiduguri metropolitan local government areas (LGAs) of Borno state, Nigeria. Methodology: Self-administered questionnaires were issued to HCWs attending a workshop on child spacing counselling and service organized by the Society of Gynaecology and Obstetrics of Nigeria, North-East sector (SOGON-NE). The questionnaire inquired about knowledge, attitudes and practice of emergency contraception. Results: Eighty-nine (89.0%) of the respondents were aware of EC and 88.0% have approved of its provision. The most common indication for the EC was unprotected sexual intercourse (91.0%), followed by rape, failed contraception and missed pills. Sixty-five (84.4%) of Nurse/Midwives and CHEWs were willing to provide EC for prospective clients and 59(76.6%) of them had provided EC in the past. The commonest form of EC known to the respondents was Levonorgestrel (Postinor 2), followed by oral contraceptive pills (OCP) and intrauterine device (IUCD). Mifepristone and ulipristal were known to only 23.6% and 11.2% of the respondents respectively. Majority (79.6%) will give EC immediately after intercourse. Only 46.1% of the respondents would institute EC within 7 days of unprotected intercourse and among them, 50% were Nurse/Midwives and 46.4% were CHEWs. Conclusion: Both the knowledge and approval of EC among the HCWs in the IDP camps and host community clinics in Jere and Maiduguri metropolitan LGAs of Borno state are high. This can be harnessed to encourage the wide utilization of the EC by adolescents and other vulnerable women in the IDP camps and host communities.